2016
DOI: 10.1140/epjb/e2016-60781-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the classical spin-ice model with nearest neighbour interactions using the Wang-Landau algorithm

Abstract: In this article we study the classical nearest-neighbour spin-ice model (nnSI) by means of Monte Carlo simulations, using the Wang-Landau algorithm. The nnSI describes several of the salient features of the spin-ice materials. Despite its simplicity it exhibits a remarkably rich behaviour. The model has been studied using a variety of techniques, thus it serves as an ideal benchmark to test the capabilities of the Wang Landau algorithm in magnetically frustrated systems. We study in detail the residual entropy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…[21], which remains unclear. Finally, in 2016, Ferreyra et al [26], used Wang-Landau (WL) simulations in nearest-neighbor spin-ice to give an estimate of the residual density of states, which is also in accordance with Nagle's estimate.…”
Section: Numerical Workmentioning
confidence: 77%
“…[21], which remains unclear. Finally, in 2016, Ferreyra et al [26], used Wang-Landau (WL) simulations in nearest-neighbor spin-ice to give an estimate of the residual density of states, which is also in accordance with Nagle's estimate.…”
Section: Numerical Workmentioning
confidence: 77%
“…A parallel WL method based on the replica-exchange framework for Monte Carlo simulations was also proposed [13]. Recently, Ferreyra et al [14] reported the calculation of g(E) for the Ising model on the pyrochlore lattice using the WL method.…”
Section: +mentioning
confidence: 99%
“…Unlike spin ice models, our model "water oxygens" possess interacting dipoles, whereas the only interaction between hydrogens ("spins") comes from the topological IR constraints. These analogies and differences underpin those that will appear in the equilibrium phase diagram, reminiscent of but not identical to the three-dimensional (3D) Kasteleyn transition (31) of spin ice in a field (32,33), as well as to the out-of-equilibrium, proton ordering behavior. The kinetic process by which the dopant triggers proton ordering is an avalanche of proton hoppings, which, breaking up closed rings, generates strings of collinear hydrogen bonds, all pointing in the same direction along a winding line, thus upsetting the ring landscape of the disordered phase.…”
Section: Significancementioning
confidence: 87%
“…1 D, Inset. Pauling's entropy is known to be only a lower bound (33). Our HREM calculations capture the addi-tional proton correlations along the closed rings, which cause entropy to rise higher for smaller sizes (40).…”
Section: Modelmentioning
confidence: 98%